Rapid, conformal gas-phase formation of silica (SiO2) nanotubes from water condensates - Bae, Changdeuck; Kim, Hyunchul; Yang, Yunjeong; Yoo, Hyunjun; Moreno, Josep M. Montero; Bachmann, Julien; Nielsch, Kornelius; Shin, Hyunjung (Nanoscale, 2013)
An innovative atomic layer deposition (ALD) concept, with which nanostructures of water condensates with high aspect ratio at equilibrium in cylindrical nanopores can be transformed uniformly into silica (SiO2) at near room temperature and ambient pressure, has been demonstrated for the first time. As a challenging model system, we first prove the conversion of cylindrical water condensates in porous alumina membranes to silica nanotubes (NTs) by introducing SiCl4 as a metal reactant without involving any catalytic reaction. Surprisingly, the water NTs reproducibly transformed into silica NTs, where the wall thickness of the silica NTs deposited per cycle was found to be limited by the amount of condensed water, and it was on the orders of ten nanometers per cycle (i.e., over 50 times faster than that of conventional ALD). More remarkably, the reactions only took place for 10-20 minutes or less without vacuum-related equipment. The thickness of initially adsorbed water layers in cylindrical nanopores was indirectly estimated from the thickness of formed SiO2 layers. With systematic experimental designs, we tackle the classical Kelvin equation in the nanosized pores, and the role of van der Waals forces in the nanoscale wetting phenomena, which is a long-standing issue lacking experimental insight. Moreover, we show that the present strategy is likely generalized to other oxide systems such as TiO2. Our approach opens up a new avenue for ultra-simple preparation of porous oxides and allows for the room temperature formation of dielectric layers toward organic electronic and photovoltaic applications.